Three faces of antisemitism - Herf, Jeffrey, 1947- author.
1 online resource (xv, 269 pages).
Keywords: "Three Faces of Antisemitism examines the three primary forms of antisemitism as they emerged in modern and contemporary Germany, and then in other countries. Essays draw on the author's historical scholarship over the years on the form antisemitism assumed on the far right in Weimar and Nazi Germany, in the Communist regime in East Germany, and in the West German radical left, and in Islamist organizations during World War II and the Holocaust, and afterwards in the Middle East. The resurgence of antisemitism since the attacks of September 11, 2001 has origins in the ideas, events and circumstances in Europe and the Middle East in the half century from the 1920s to the 1970s. This book covers the period since 1945 when neo-Nazism was on the fringes of Western and world politics, and the persistence of antisemitism took place primarily when its leftist and Islamist forms combined antisemitism with anti-Zionism in attacks on the state of Israel. The collection includes recent essays of commentary that draw attention to the simultaneous presence of antisemitism's three faces. While scholarship on the antisemitism of the Nazi regime and the Holocaust remains crucial, the scholarly, intellectual and political effort to fight antisemitism in our times requires examination of antisemitism's leftist and Islamist forms as well. This book will be of interest to scholars researching antisemitism, racism, conspiracy theories, the far right, the far left, and Islamism"--